New Islamic School Civilization in Education Curriculum in Digital Era - Suprianto, Bibi; Sari, Cut Manda (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
The civilization of Islamic schools within the educational curriculum in the digital era has depicted the advancement of Islamic education in the digitalization of education. The discussion regarding the curriculum of Islamic education in the context of the new Islamic school civilization in the digital era is an intriguing context to observe. This study argues that the emerging civilization of Islamic schools in the curriculum of Islamic education in the digital era has indeed provided innovation and contributed to technology-based Islamic education in Muslim schools. This study raises the question of how the form of the new civilization of Islamic schools is evolving within the curriculum of education in the digital era. To answer this question, the study employs qualitative research with a media approach for in-depth research analysis. The findings of this study demonstrate that the new civilization of Islamic schools in the curriculum of Islamic education not only imparts religion-based education but also teaches Islamic education based on the digitalization of technology and science. This study recommends the importance of conducting interviews on digital-based Islamic education in other schools to gain a more reflective and subjective understanding of the meaning of the new civilization of Islamic schools in the curriculum of Islamic education in the digital era.